Tinjauan Kritis Studi Life Cycle Assessment (LCA) di Indonesia - Mochammad Chaerul; Venessa Allia (Fakultas Teknik, 2020)
Life Cycle Assessement (LCA) studies in Indonesia have developed since last few years with a various product system studied. This paper aims to provide a critical review of LCA studies that have been performed in Indonesia, which is expected to improve the quality of study in Indonesia in the future. Scope of the study was limited to papers published in national journals and traced through the Indonesian Publication Index website from year of 2010 to 2016. There were 17 LCA studies reviewed, including the studies for renewable energy products, plantation, waste management, water treatment, and several products’ manufacturing etc. Various critical issues found that need further attention to improve the quality of research LCA including the narrow LCA boundary, functional units, data inventory and allocation procedures, the conclusion that exceeds the results of the study, application of uncertainty analysis and sensitivity analysis, and transparency of the report.